Exposición urbana no ocupacional al plomo y niveles sanguíneos en mujeres embarazadas y en recién nacidos, Mérida, Venezuela (2000)
ABSTRACT: Studies of forty-two pregnant women (21 occupationally exposed and 21 not-exposed), were conducted with the purpose of determining the average values of lead in the blood of pregnant women and their newborns. The levels of lead in the blood were determined using the method of spectophotomery of atomic absorption. The statistical analysis was carried out by SPSS version 7.5 for Windows, by means of percentages, frequencies, standard deviation and t analysis by the student, variability, lineal correlation and multiple regressions. The results of this study prove that significant statistical differences exist in the averages noted above, and that the risk of exposure influences the level of lead in the blood of newborns and pregnant women, exceeding the permitted levels allowed by the Center of Disease Control in the United States of America. As such, there exists an high and statistically significant correlation between the level of lead in mothers and their newborn infants. The variable levels of lead in the mother is a good predictor of the variable levels of lead in their newborns.